2005
DOI: 10.1038/modpathol.3800466
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation characteristics in pediatric Hodgkin's lymphoma point to a cell cycle arrest in the G1 phase

Abstract: This study was undertaken to determine the prognostic relevance of the proliferation rate in neoplastic cells in children and adolescents with Hodgkin's lymphoma. Paraffin-embedded biopsy specimens were immunostained with the proliferation-associated monoclonal antibodies Ki-S5 (Ki-67 antigen) and Ki-S2 (which detects the repp86 protein). Repp86 is a protein of about 100 kDa encoded by a gene located on human chromosome band 20q11.2. In contrast to the Ki-67 antigen, repp86 expression is restricted to the cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 34 publications
0
5
0
1
Order By: Relevance
“…In human testis, spermatogonia and spermatocytes express CT45 antigen and harbor the Ki-67 antigen, a protein only expressed in proliferating cells from G 1 until the end of mitosis (31). Immunostainings of Hodgkin's lymphoma with a mAb specific to the Ki-67 antigen showed that f80% of the Hodgkin and Reed-Sternberg cells were at least in G 1 cell cycle phase, showing that CT45 antigen expression is probably associated with cell proliferation in these cells (32). Nuclear expression of CT45 in a small fraction of resting cells of the Hodgkin's cell line L428 could be a consequence of the process of cell culturing.…”
Section: Discussionmentioning
confidence: 99%
“…In human testis, spermatogonia and spermatocytes express CT45 antigen and harbor the Ki-67 antigen, a protein only expressed in proliferating cells from G 1 until the end of mitosis (31). Immunostainings of Hodgkin's lymphoma with a mAb specific to the Ki-67 antigen showed that f80% of the Hodgkin and Reed-Sternberg cells were at least in G 1 cell cycle phase, showing that CT45 antigen expression is probably associated with cell proliferation in these cells (32). Nuclear expression of CT45 in a small fraction of resting cells of the Hodgkin's cell line L428 could be a consequence of the process of cell culturing.…”
Section: Discussionmentioning
confidence: 99%
“…However, an immunohistochemical study of 224 pediatric patients enrolled in the German Society for Pediatric Oncology and Hematology (GPOH) HD-90 and HD-95 trials found that high Ki-67 expression in HRS cells as well as lymphocytic and histiocytic cells was not related to either advanced clinical stage or poor clinical outcome. Meanwhile, expression of the cell cycle marker repp86, which generally becomes detectable at the G1-S boundary, was low, implying that HRS or lymphocytic and histiocytic cells are arrested in the G1 phase of the cell cycle [41]. Better outcomes in pediatric HL cases that have a high proliferative index are attributed to increased susceptibility of proliferative cells to chemotherapeutic drugs [17, 42, 43].…”
Section: Molecular and Genetic Prognostic Biomarkersmentioning
confidence: 99%
“…Although we did not examine the proliferation rates of HRS cells in this series, previous studies have reported prognostic relevance of proliferation rates of HRS cells in cHL. [47][48][49] It is conceivable that the superior survival of cHL with MET and/or MST1R expression in the present study may also involve higher proliferation rate of HRS cells. In our study, MET or MST1R protein correlated with each level of mRNA.…”
Section: Discussionmentioning
confidence: 76%